Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Dis/ability studies: theorising disablism and ableism - Goodley, Dan (Routledge, 2014)
In this ground-breaking new work, Dan Goodley makes the case for a novel, distinct, intellectual, and political project – dis/ability studies – an orientation that might encourage us to think again about the phenomena of disability and ability. Drawing on a range of interdisciplinary areas, including sociology, psychology, education, policy and cultural studies, this much needed text takes the most topical and important issues in critical disability theory, and pushes them into new theoretical territory. Goodley argues that we are entering a time of dis/ability studies, when both categories of disability and ability require expanding upon as a response to the global politics of neoliberal capitalism. Divided into two parts, the first section traces the dual processes of ableism and disablism, suggesting that one cannot exist without the other, and makes the case for a research-driven and intersectional analysis of dis/ability. The second section applies this new analytical framework to a range of critical topics, including: The biopolitics of dis/ability and debility Inclusive education Psychopathology Markets, communities and civil society. Dis/ability Studies provides much needed depth, texture and analysis in this emerging discipline. This accessible text will appeal to students and researchers of disability across a range of disciplines, as well as disability activists, policymakers, and practitioners working directly with disabled people.
Section: xvii, 204 pages ; 25 cm
Keywords: EDI; approches et analyses; capacitisme; care; corps; cours; discipline; interdisciplinarité; lit4700; premier cycle; psychologie; pédagogie; santé; sciences de l'éducation; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

Contre l'indifférence des privilégiés : à quoi sert le care - Gilligan, Carole; Hochschild, Arlie; Tronto, Joan (Payot, 2013)
Comment résister à l'injustice ? Peut-on vaincre le " capitalisme émotionnel " ? Une éthique du care globale est-elle possible à l'heure des migrations transnationales ? Réunies pour la première fois, trois féministes et pionnières de la théorie et de l'éthique du care, la psychologue Carol Gilligan, la sociologue Arlie Hochschild et la politiste Joan Tronto, apportent leurs éléments de réponse avec, en ligne de mire, une injonction : encourager chacun à prendre ses responsabilités pour agir contre l'indifférence des privilégiés. Un événement intellectuel.
Keywords: approches et analyses; care; discipline; division sexuelle du travail; genre; patriarcat; privilèges; psychologie; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; éthique

Pascale Molinier, Le travail du care - Volery, Ingrid (La nouvelle revue du travail, 2013)
Paru aux Éditions La Dispute en 2013, le dernier ouvrage de Pascale Molinier s’attelle à ouvrir la boite noire du care, tel qu’il se déploie dans le quotidien d’un EHPAD de la région parisienne (renommé Villa Plénitude). S’inscrivant dans la lignée des travaux de psychologie et de philosophie qui en ont tenté une formalisation outre-Atlantique, son principal apport est de donner chair à une notion devenue « tarte-à-la-crème », en l’ancrant dans la réalité de situations professionnelles qui dé...
Keywords: care; discipline; europe; france; philosophie; projet charge mentale; psychologie; régions géographiques; sciences humaines; soins aux personnes âgées; thématiques; travail